Rab33a Mediates Anterograde Vesicular Transport for Membrane Exocytosis and Axon Outgrowth - Nakazawa, Hitomi (J Neurosci, 2012)
Axon outgrowth requires plasma membrane expansion, which results from post-Golgi vesicular transport and fusion. However, the molecular mechanisms regulating post-Golgi vesicular trafficking for membrane expansion and axon outgrowth remain unclear. Here, we show that Rab33a expression became upregulated during axon outgrowth of cultured rat hippocampal neurons. Rab33a was preferentially localized to the Golgi apparatus and to synaptophysin-positive vesicles that are transported along the growing axon. Previous studies showed that synaptophysin is localized to post-Golgi vesicles transported by fast axonal transport in developing neurons. Reduction of Rab33a expression by RNAi (RNA interference) inhibited the anterograde transport of synaptophysin-positive vesicles, leading to their decrease in axonal tips. Furthermore, this treatment reduced membrane fusion of synaptophysin-positive vesicles at the growth cones and inhibited axon outgrowth. Overexpression of Rab33a, on the other hand, induced excessive accumulation of synaptophysin-positive vesicles and concurrent formation of surplus axons. These data suggest that Rab33a participates in axon outgrowth by mediating anterograde axonal transport of synaptophysin-positive vesicles and their concomitant fusion at the growth cones.